Salt damage risk prediction for porous limestone - Derluyn, H. (2014)
We present a model coupling heat, moisture and salt transport, salt crystallization, deformation and damage in porous building materials with the aim of predicting crystallization-induced damage. The model performance is illustrated by simulating the damage caused by sodium chloride crystallization in a porous limestone. The results are compared with experimental observations based on neutron and X-ray imaging, showing a good agreement. The effective stresses that can cause damage are the result of the crystallization pressure combined with a sufficient amount of precipitating salt crystals in a localized zone.